2021
DOI: 10.1186/s12958-021-00820-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of miR-30d-5p and SOCS1 in patients with recurrent implantation failure during implantation window

Abstract: Background Poor endometrial receptivity is a major factor that leads to recurrent implantation failure. However, the traditional method cannot accurately evaluate endometrial receptivity. Various studies have indicated that microRNAs (miRNAs) are involved in multiple processes of embryo implantation, but the role of miRNAs in endometrial receptivity in patients with recurrent implantation failure (RIF) remains elusive. In the present study, we investigated the presence of pinopodes and the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…However, their role in endometrial receptivity in women experiencing RIF remains unclear. The expression levels of miR-30d-5p in the endometrium were decreased during the implantation window, and it was observed that miR-30d-5p suppresses cytokine signaling 1 (SOCS1) and LIF expression, contributing to the pathophysiology of RIF [ 79 ]. Another miRNA, miR-185b, has been observed to be associated with implantation failure by disrupting HOXA10 expression.…”
Section: Resultsmentioning
confidence: 99%
“…However, their role in endometrial receptivity in women experiencing RIF remains unclear. The expression levels of miR-30d-5p in the endometrium were decreased during the implantation window, and it was observed that miR-30d-5p suppresses cytokine signaling 1 (SOCS1) and LIF expression, contributing to the pathophysiology of RIF [ 79 ]. Another miRNA, miR-185b, has been observed to be associated with implantation failure by disrupting HOXA10 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the other hub miRNAs have also been reported to be associated with embryo implantation failure. Evidence show that miR-30d-5p plays important role in embryo implantation [ 32 35 ]. Human endometrium can secrete miR-30d which is further taken up by the pre-implantation embryo [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-30d knock-out mice induced a significant downregulation of endometrial receptivity markers and had poorer implantation rates than wild-type embryos [ 32 ]. The expression of miR-30d-5p was significantly decreased in the endometrium of patients with RIF during WOI [ 35 ]. While miR-6731-5p and miR-5001-3p have not been reported to be associated with embryo implantation, so far.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason behind this unexpected result remains to be investigated, it is possible that a balanced LIF/LIFR signal is critical for successful pregnancies; both too little and too much LIF production can cause infertility. A prolonged strong LIF signal may trigger activation of a negative feedback pathway mediated by SOCS, subsequently promoting degradation of receptors, leading to implantation failure ( Carvalho et al., 2014 ; Zhao et al., 2021 ). Furthermore, implantation is a complex and highly organized process that involves active crosstalk between a receptive uterus and a competent blastocyte in a time- and location-specific manner ( Kim and Kim, 2017 ).…”
Section: The Role Of Lif/lifr In the Female Reproductive Systemmentioning
confidence: 99%